Transparency, Specialization and FDI - Assaf Razin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2004)
We develop a simple information-based model of FDI flows. On the one hand, the relative abundance of intangible capital in specialized industries in the source countries, which presumably generates expertise in screening investment projects in the host countries, enhances FDI flows. On the other hand, host-country relative corporate-transparency diminishes the value of this expertise, thereby reducing the flow of FDI. The model also demonstrates that the gains for the host country from foreign direct investment [over foreign portfolio investment (FPI)] are reflected in a more efficient size of the stock of domestic capital and its allocation across firms. These gains are shown to depend crucially (and positively) on the degree of competition among FDI investors.
Keywords: F10; 330